263 INFORMING INTERVENTION DESIGN IN COGNITIVELY IMPAIRED POPULATIONS: LESSONS LEARNED FROM THE OPTIMIZE DEPRESCRIBING INTERVENTION. (25th October 2022) - Sheehan, OC; Bayliss, EA; Green, AR; Drace, ML; Norton, J; Reeve, E; Shetterly, SS; Gleason Kathy, S; Weffald, LA; Maciejewski, ML; Kraus, C; Maiyani, M; et al.
Abstract: Background: Polypharmacy is common in older adults with cognitive impairment and multiple chronic conditions increasing their risks of adverse drug events, hospitalization, further cognitive decline and death and leading to higher health care costs. Deprescribing, the process of reducing or stopping potentially inappropriate medications may improve outcomes. The OPTIMIZE trial examined whether educating and activating patients, family and clinicians about deprescribing reduces number of medications for older adults with cognitive impairment and multiple chronic conditions. Acceptability and challenges of intervention delivery in this vulnerable population are not well understood. Methods: We explored mechanisms of intervention effectiveness through post hoc qualitative interviews and surveys with 15 patients, 7 family caregivers, and 28 clinicians. We assessed accessibility and delivery of materials as well as the ability of the materials to facilitate conversations and influence decisions around deprescribing. Results: Acceptance of the intervention was affected by contextual factors including cognition and prior knowledge of deprescribing. Positive effects of the intervention included patients scheduling specific appointments to discuss deprescribing and providers being prompted to consider deprescribing. Recollection of intervention materials by patients was inconsistent but highest shortly after intervention delivery. Short clinic visit times remained the largest clinician barrier to deprescribing. Conclusion: Our work identifies key learnings in intervention roll out which can guide future scaling of our intervention and other pragmatic deprescribing intervention studies in patients with cognitive impairment. We highlight the critical roles of both timing and repetition in intervention delivery to cognitively impaired populations as well as the barrier to deprescribing posed by short clinic consultation time. Our success in activating deprescribing conversations in this population highlights the need to incentivize medical professionals and health systems to incorporate deprescribing into routine clinical practice and expand proven interventions to other vulnerable populations.